VD_FINDINFO HC / 2009 / 49 vom 29. April 2009 - VD Tribunal cantonal (2009)
BAIL À LOYER, ANNULABILITÉ, RÉSILIATION, LOYER ABUSIF, RÉNOVATION D'IMMEUBLE | 269a let. a CO, 271 al. 1 CO, 274d al. 3 CO, 452 CPC, 465 al. 1 CPC, 11 OBLF